Literature and complaint in England, 1272-1553 - Scase, Wendy (Oxford University Press, 2007)
Giving a different perspective on the relations between early judicial process & the development of literature in England, this book argues that texts ranging from political libels & pamphlets to laments of the unrequited lover constitute a literature shaped by the crucial role of complaint in the law courts.